INTESTINAL PARASITISM IN PUCCHUN'S PRIMARY SCHOOL STUDENTS, PREVALENCE AND EPIDEMIOLOGY FACTORS, AREQUIPA-PERÚ 2006 - Casquina-Guere, Liz (2011)
The present study was done, from May to August 2006 in Pucchun, a town located in Arequipa-Peru, Camana Province, Mariscal Caceres District. One fecal sample and epidemiological dates were obtained from each of Pucchun's Primary School students. Fecal samples were processed by modified Teleman technique and fast sedimentation. 92.68% of samples had one or more intestinal parasites, predominantly protozoa: Entamoeba histolytica/ Entamoeba dispar (33.17%), Giardia intestinalis (31.71%), Hymenolepis nana (47.17%), Diphyllobothrium pacificum (0.49%) and Fasciola hepatica (0.49%). Polyparasitism (42.63%) was more frequently encountered. Non pathogen parasites were also present and included Entamoeba coli (72.68%), Blastocystis hominis (48.29%), Endolimax nana (35.61%), Iodamoeba butschlii(23.90%), and Chilomastix mesnilli (16.58%). Epidemiological factors found were: age between 8 and 10 years, inadequate form and place of rubbish elimination, presence of rodents and vectors in houses and eating uncooked vegetables.